La contribució de la teoria del flogiste a l’estructuració actual de la ciència química. Implicacions didàctiques - Izquierdo i Aymerich, Mercè (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this article, the meaning of the Theory of Plogiston is analyzed in the context of the period in which it was formulated. Certain aspects of this theory, which contributed to the structuring of modern concepts of Chemistry are pointed out, as is the inappropriateness of linking this theory to a dark period of the Science of Chemistry —a step back from a former situation— overcome thanks to A.L. Lavoisier, who rejected the theory. Similarly, it must be taken into account that some of the children's ideas about chemical phenomena, though not coincidental with currently accepted scientific theories, are valid starting points for planning an appropriate learning strategy which will lead to the understanding of present-day science.